Digital technologies in built environment projects: Review and future directions - Papadonikolaki, E., Krystallis, I. and Morgan, B. (Project Management Journal)
Through a systematic literature review we explore how digital technologies reshape and catalyze digital innovations in the built environment$1 (Ba highly project-based setting. We analyzed circa 3,000 titles, further narrowed down to 87 articles. We synthesized an original framework for data analysis. The article presents implications for the deployment of digital technologies on three levels: individuals, organizations, and projects. Whereas most of these studies examined the impact of digital innovation in projects, recommendations focused on organizations, suggesting future directions for performance measurement, developing capabilities of firms to manage changes in dynamic environments and interorganizational settings.- Reproduced s
Keywords: Digital transformation, Systemtic literature review, Innovation, organization, Proejctes, Induviduals